Working Capital Management Practices of Bakeshops in Selected Cities of Metro Manila - Christopher Bagaconza (Fakultas Bisnis - Institut Bio Scientia International Indonesia, 2025)
The main objective of the study is to assess the level of effectiveness of working capital management practices of bakeshops in Marikina City and Pasig City. The study specifically addressed the following problems: (1) Firm’s profile of the respondents according to number of years in operation, number of employees, capitalization, source of capitalization, and average monthly sales, and individual profile according to age, sex, highest education attainment, and number of related trainings/seminars attended for the last three years.; (2) Respondents’ assessment on the level of effectiveness of the working capital management practices in terms of Cash Management, Receivable Management, Payable Management, and Inventory Management; and (3) Significant difference in the respondents’ assessment on the level of effectiveness of working capital management practices when grouped according to profile. This study utilized the descriptive-survey method of research through survey questionnaire which involved 156 registered bakeshops. Majority of the respondents were between 24 to 39 years old, male, had attained college degree, attended 1 to 2 related trainings/seminars for the past three years, more than 6 years in the business with 3 to 5 employees, and operated with a capitalization of Php 50,000 sourced from self-funding with Php 50,000 average monthly sales. On the level of assessment on effectiveness of the working capital management practices, the respondent’s perception on all aspects was all effective. The researcher provided recommendations on the improvement of working capital management practices in view of bakeshop owners, local government unit, aspiring entrepreneurs, and future research.